REMOVAL OF HEAVY METALS FROM POLLUTED DUG-WELL WATER (CASE STUDY: IN YOGYAKARTA URBAN AREA) BY UTILIZING ACTIVATED ZEOLITE AND BENTONITE IN ADSORPTION EXPERIMENT - , Bunchoeun PICH; , I Wayan WARMADA; , Heru HENDRAYANA; , Tetsuro YONEDA ([Yogyakarta] : Ikatan Ahli Geologi Indonesia, 2008)
Due to human activities such as batik home industries, abattoirs, and tanneries, the existence of heavy metals in dug-well water has been known as the cause of groundwater pollution in Yogyakarta City. To treat this dug-well water, a batch adsorption experiment by utilizing the activated zeolite and bentonite was carried out. Prior to the treatment, the zeolite and bentonite were characterized by means of XRD, SEM, XRF, and various ICP and modified to improve their CECs by thermal activation process, whereas the dug-well water was initially analyzed for certain heavy metals like Cd, Cu, Fe, Zn, Pb by AAS. In the course of treatment, the activated zeolite and bentonite powders at the same amount of 1g, 2g, 4g, 8g, and 15 g were separately put into the natural dug-well water sample of 250 ml